Identification, characterization and immunological analysis of Ras related C3 botulinum toxin substrate 1 (Rac1) from grass carp Ctenopharyngodon idella. Issue 1 (January 2016) - Hu, Mo-Yan; Shen, Yu-Bang; Xu, Xiao-Yan; Yu, Hong-Yan; Zhang, Meng; Dang, Yun-Fei; Li, Jia-Le
Abstract: Rac1, a Rho GTPase, serves critical immunological functions in mammals. Here, a Rac1 homolog ( gcRac1 ) was identified in grass carp ( Ctenopharyngodon idella ). The full-length 2023-base pair gcRac1 cDNA contained a 579-bp open reading frame encoding a 192-residue protein, including a conserved RHO domain and nuclear localization signal. The gcRac1 protein shares high identity with other Rac1 counterparts and phylogenetically clustered with Danio rerio Rac1. The gcRac1 transcript showed wide tissue distribution and was inducible by Aeromonas hydrophila in vivo and in vitro ; its expression also fluctuated with LPS or flagellin stimulation in vitro . With gcRac1 over-expression, gcPAK1, gcIL1-β, gcTNF-α and gcIFN were basically up-regulated by A. hydrophila and bacterial PAMPs induction, while gcRac1 knockdown decreased these transcripts after A. hydrophila challenge. Over-expression of gcRac1 reduced, while its suppression facilitated, bacterial invasion. Moreover, gcRac1 could activate NF-κB signaling. These findings implicate the vital role of gcRac1 in grass carp innate immunity. Highlights: A Rac1 gene was identified from grass carp Ctenopharyngodon idella . Over-expression of gcRac1 induces IL1-β, TNF-α and IFN during pathogen stimulation. Knocking down gcRac1 inhibits PAK1, IL1-β, TNF-α, IFN post Aeromonas hydrophila infection. gcRac1 can induce NF-κB activity. gcRac1 induces an effective immune response against A. hydrophila invasion in vitro .